Hubungan Pengetahuan tentang HIV/AIDS dengan Sikap dan Tindakan Penggunaan Kondom Pria pada Wanita Pekerja Seks di Kota Manado - Juliastika, Juliastika; Korompis, Grace E. C.; Ratag, Budi T. (Sam Ratulangi University, 2012)
Currently HIV/AIDS is growing, including in Indonesia, until March 2011 AIDS cases had reached 24.482 cases in Indonesia (Ditjen PPM & PL, 2011). Risk factors for HIV/AIDS is a heterosexual. Prevention efforts on high risk groups, especially female sex workers is to increase knowledge about HIV/AIDS so that they eventually want to change attitudes and behavior to prevent transmission og HIV/AIDS.The purpose of this reseach was to determine there is a related of knowledge about HIV/AIDS with the attitude and actions of male condom use in female sex workers in Manado with a sample size of 71 respondents. This reseach is a cross sectional study that is analytical with the respondents were female sex workers.Results showed that most respondents had knowledge about knowledge about HIV/AIDS (53,52%), good attitude toward condom use (64,79%), and has the action did not always use condoms (66,19%). The results of bivariate analysis showed that variables significantly associated with no knowledge of the attitude variable (p = 0,092) and the variable knowledge about HIV/AIDS showed a significant association with the act of respondents in use of condoms (p = 0,022).According to the results of the reseach, the suggestions put forward in particular to the management tackling HIV/AIDS is improvement knowledge about HIV/AIDS and condom use effective and intensively so as to change the attitude and action for going better.Â ABSTRACTPenyakit HIV/AIDS semakin berkembang di Indonesia dan hingga Maret 2011 kasus AIDS telah mencapai 24.482 kasus (Ditjen PPM & PL, 2011). Faktor risiko HIV/AIDS terbanyak adalah heteroseksual. Upaya pencegahan pada kelompok berisiko tinggi khususnya wanita pekerja seks adalah meningkatkan pengetahuan tentang HIV/AIDS sehingga akhirnya dapat mengubah sikap dan perilaku untuk mencegah penularan HIV/AIDS.Tujuan diadakannya penelitian ini adalah untuk mengetahui apakah terdapat hubungan pengetahuan tentang HIV/AIDS dengan sikap dan tindakan penggunaan kondom pria pada wanita pekerja seks di Manado dengan jumlah sampel 71 responden. Penelitian ini adalah penelitian potong lintang yang bersifat analitik dengan responden adalah wanita pekerja seks.Hasil penelitian menunjukkan bahwa pengetahuan sebagian besar responden mempunyai pengetahuan kurang tentang HIV/AIDS (53,52%), sikap baik terhadap penggunaan kondom (64,79%), dan mempunyai tindakan tidak selalu menggunakan kondom (66,19%). Hasil analisis bivariat menunjukkan bahwa variabel pengetahuan tidak berhubungan bermakna dengan variabel sikap (p = 0,092) dan variabel pengetahuan tentang HIV/AIDS menunjukkan hubungan yang bermakna dengan tindakan reponden dalam penggunaan kondom (p = 0,022).Disarankan untuk pengelola program penanggulangan HIV/AIDS agar dilakukan peningkatan pengetahuan tentang HIV/AIDS dan penggunaan kondom secara efektif dan intensif sehingga mampu mengubah sikap dan tindakan menjadi lebih baik.